Effects of a 4-Week Plyometric Box Jump Training Program on 50m Breaststroke Performance in Competitive Swimmers - Indri Patricia A Sinaga; Yagmur Tosun; Samsuddin Siregar; Jet C. Longakit (Inspiree)
The  purpose  of  the study. The objective of this study is to examine the influence of a four-week plyometric box jump training regimen on the performance of competitive swimmers in the 50m breaststroke event, with a particular focus on evaluating alterations in sprint duration, stroke mechanics, and power output.